Controlling Two‐Step Multimode Switching of Dihydroazulene Photoswitches. Issue 10 (14th January 2015) - Petersen, Anne U.; Broman, Søren L.; Olsen, Stine T.; Hansen, Anne S.; Du, Lin; Kadziola, Anders; Hansen, Thorsten; Kjaergaard, Henrik G.; Mikkelsen, Kurt V.; Brøndsted Nielsen, Mogens
Abstract: We present the synthesis and switching studies of systems with two photochromic dihydroazulene (DHA) units connected by a phenylene bridge at either para or meta positions, which correspond to a linear or cross‐conjugated pathway between the photochromes. According to UV/Vis absorption and NMR spectroscopic measurements, the meta ‐phenylene‐bridged DHA–DHA exhibited sequential light‐induced ring openings of the two DHA units to their corresponding vinylheptafulvenes (VHFs). Initially, the VHF–DHA species was generated, and, ultimately, after continued irradiation, the VHF–VHF species. Studies in different solvents and quantum chemical calculations indicate that the excitation of DHA–VHF is no longer a local DHA excitation but a charge‐transfer transition that involves the neighboring VHF unit. For the linearly conjugated para ‐phenylene‐bridged dimer, electronic communication between the two units is so efficient that the photoactivity is reduced for both the DHA–DHA and DHA–VHF species, and DHA–DHA, DHA–VHF, and VHF–VHF were all present during irradiation. In all, by changing the bridging unit, we can control the degree of stepwise photoswitching. Abstract : Identical but not the same : Two dihydroazulene photoswitches separated by a meta ‐phenylene bridge can be opened sequentially to vinylheptafulvenes under the influence of light as the intermediate species experiences reduced photoactivity owing to a charge‐transfer quenching mechanism (see scheme). Such stepwise ring openings were not observed when the units were instead separated by a para ‐phenylene bridge.